Preparation and characterization of clay bonded high strength silica refractory by utilizing agriculture waste; [Preparación y caracterización de sílice refractaria de alta resistencia unida a arcilla utilizando residuos agrícolas] - Bhardwaj A.; Hossain S.K.S.; Majhi M.R. (My University, 2025)
Clay bonded silica refractory was prepared by utilizing agriculture waste called rice husk ash (RHA) and refractory grog. Various samples were prepared with different compositions based upon partial replacement of quartz by RHA. Rectangular samples were prepared by following semi dry process prior to pressing in a uniaxial hydraulic press and sintering at a temperature of 1200 °C in air atmosphere. Various physical, mechanical and thermal characterizations were done like X-ray diffraction (XRD), scanning electron microscope (SEM), apparent porosity (AP), bulk density (BD), cold crushing strength (CCS), refractoriness and thermal conductivity measurement. The sample utilizing 30% of RHA was considered most optimum composition which produced cold crushing strength of 38 MPa and thermal conductivity of 2.08 W/m K at 800 °C with a considerable good refractoriness. Enhancement in the mechanical as well as thermal properties may be considered as attributed to the amorphous silica which has reacted more easily and efficiently with other material surrounding giving rise to the densification and produced stable crystalline phase to the refractory material. These promising characteristics suggests that the RHA may lead to be used as a potential material for the preparation of clay bonded high strength silica refractories. © 2017